2019
DOI: 10.1016/j.heliyon.2019.e01907
|View full text |Cite
|
Sign up to set email alerts
|

Echographic and physical characterization of albumin-stabilized nanobubbles

Abstract: There has been increasing interest in using nanobubbles (NBs) for ultrasound mediated drug delivery as well as for ultrasound imaging. Albumin NBs are especially attractive for its potential of becoming a versatile platform for drug carriers and molecular targeted therapy agents. However, physical characterization of NBs is generally considered to be difficult due to various technical issues, such as concentration limitations, nanoparticle contamination, etc. In the present study, we measured the size distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…We showed that the albumin NBs had lower inertial cavitation threshold than lipid shelled NBs in an in vitro cell suspended experiment setup. Results suggested that albumin NBs irradiated with 0.8–1.0 W/cm 2 intensity ultrasound tended to easily collapse and enhanced cancer cell disruption by up to 6.8 fold compared to ultrasound alone ( Watanabe et al, 2019 ). Furthermore, we demonstrated gene transfer into in vitro attached cell culture monolayers and in mice by albumin stabilized NBs in conjunction with a hand-held portable ultrasound imaging device ( Kida et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that the albumin NBs had lower inertial cavitation threshold than lipid shelled NBs in an in vitro cell suspended experiment setup. Results suggested that albumin NBs irradiated with 0.8–1.0 W/cm 2 intensity ultrasound tended to easily collapse and enhanced cancer cell disruption by up to 6.8 fold compared to ultrasound alone ( Watanabe et al, 2019 ). Furthermore, we demonstrated gene transfer into in vitro attached cell culture monolayers and in mice by albumin stabilized NBs in conjunction with a hand-held portable ultrasound imaging device ( Kida et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human serum albumin-based NBs were prepared according to previous studies reported elsewhere ( Lafond et al, 2018 ; Watanabe et al, 2019 ; Kida et al, 2020 ). Briefly, the air in a plastic container tube (height: 30 mm, outer diameter: 25 mm) was replaced with 15 ml of perfluoropropane gas (C 3 F 8 ; Takachiho Chemical Industrial, Tokyo, JP) using a 23-gauge needle inserted through a small opening in a custom made cap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic passive cavitation detectors indicated that inertial cavitation threshold was lower than the commercially available MB US contrast agents. Watanabe et al (2019) similarly conducted a detailed study of albumin-based NBs by 3 different nanoscale measurement modalities and characterized the bubble size distribution, gas/particle ratio, and concentration. Subsequently, superior contrast imaging and elevation of time signal intensity curve of the NBs were obtained in an in vitro flow vessel system driven at US frequencies of 40 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…The physical character of L-NBs and A-NBs were measured as described previously (Watanabe et al, 2019). The particle size of NBs was measured by nanoparticle tracking analysis (NTA) device (NanoSight LM10; Malvern Instruments, Worcestershire, UK).…”
Section: Characteristic Analysis Of Nanobubblesmentioning
confidence: 99%